Factors Influencing Interest in Career Selection as Financial Auditor for Accounting Students Class of 2020 During Covid-19.: Faktor yang Mempengaruhi Minat Pemilihan Karir Sebagai Auditor Keuangan Mahasiswa Akuntansi Angkatan 2020 Saat Covid-19. - Leny Ilyasari; Wiwit Hariyanto (Academia Open, 2021)
This study aims to determine whether framing, groupthink, financial rewards, social values, and job market considerations have a influence on interest in choosing a career as a financial audit at the Muhammadiyah University of Sidoarjo students in the accounting study program during the covid-19 pandemic.This study used a quatitative approach. Data collection techniques of collecting using a questionnaire. The population of this study includes all the accounting students of Muhammadiyah University of sidoarjo, batch 2020 as many as 178 students. The sampling technique used was simple random sampling, the slovin formula and obtaineda sample of 123 respondents. Method of analysis data used in thi research was multiple linear regression techniques by using the SPSS version 25 test tool .The results of this study indicate that framing, groupthink, financial rewards, social values, and job market considerations have a significant influence on interest in choosing a career as a financial auditor at the Muhammadiyah University of Sidoarjo students in the accounting study program during the Covid-19 pandemic.